Metallic Ratios : The Mathematical Relationships between different Metallic Means (JOURNAL OF ADVANCES IN MATHEMATICS, 2021)
This paper introduces the precise mathematical relationships between different Metallic Ratios. Certain distinctive mathematical correlations are found to exist between various Metallic Means. This work presents the empirical formulae those provide the exact mathematical relationships between different Metallic Ratios.